It Is Good To Be Stressed: Improving Performance And Body Responses By Stress Reappraisal - Banaszkiewicz, Mateusz (Journal of Education, Health and Sport, 2017)
Despite the commonly shared belief that effects of stress depend on the amount of stress arousal, a wide body of research derived from appraisal theory indicates that it is rather the way people think about stress what influences its’ outcomes (Akinola, Fridman, Mor, Morris, Crum, 2016; Crum, A. J., Salovey, P., Achor, S., 2013; Cohen, Sherman, 2014; Crum, A. J., Philips, D. J., 2015; Crum, Akinola, Martin, Fath, 2017; John-Henderson, Rheinschmidt, Mendoza-Denton, 2015). The aim of this paper is to put together actual research concerning psychological interventions effective in shaping adaptive cognitive and physiological responses to stress. It is focused on arousal reappraisal as a way of enhancing performance. Literature published from 1999 to 2017 was reviewed by using the following databases: EBSCO, Google Scholar, PubMed. Arousal reappraisal interventions appeared to be effective in improving performance, eliciting more adaptive physiological responses and working in experimental and real-life context. Based on presented studies possible future applications for both business and clinical area are discussed.